ANALISIS KESULITAN BELAJAR MATEMATIKA PADA PESERTA DIDIK KELAS IV DI SD NEGERI 19 SEBAMBANG TAHUN PELAJARAN 2024-2025 - Siti Nurhaliza; Parni; Bayu (JIP: Jurnal Ilmu Pendidikan, 2026)
This research began with the discovery of the phenomenon of learning difficulties experienced by students. The purpose of this research is to reveal: (1) Forms of difficulties in learning mathematics in fourth grade students of SD Negeri 19 Sebambang in the 2024-2025 academic year. (2) Teachers' efforts in overcoming difficulties in learning mathematics in fourth grade students of SD Negeri 19 Sebambang in the 2024-2025 academic year. (3) Factors causing difficulties in learning mathematics in fourth grade students of SD Negeri 19 Sebambang in the 2024-2025 academic year. This research uses a qualitative approach with a descriptive research type. Data collection techniques use interviews, observation, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and conclusions. The results of the study concluded that: (1) Difficulties in understanding mathematics problems cause students to have difficulty in determining the steps needed to solve mathematics problems given by the teacher. (2) The learning methods used are lectures, discussions, groups, inserting abstract examples during the learning process, using learning media, prinan media, and arisan shake. (3) There are two factors, namely internal factors that come from within the students themselves, such as minimal memorization of basic arithmetic operations, difficulty in completing assignments. External factors that come from outside the students themselves, namely a learning environment that is less supportive, both at school and at home.